Importancia de la gestión del departamento de consejería estudiantil y la prevención de embarazos no deseados en octavos y novenos años de educación general básica de la Unidad Educativa José Peralta de la parroquia de Mulalillo del cantón Salcedo en el año lectivo 2014 - 2015 - Iza Vilca, Sandra Marilú (2015)
The high incidence of unwanted pregnancies among adolescents and its possible prevention doing activities, processes, and knowledge, which were performed in the development of a kangaroo mothers manual. The participation of the educational institution was featured in the projection of strategies which help to reduce the high level of unintended pregnancies that occurred in adolescents. Education in general is based on the update and strengthen Curriculum which is framed in Good Living reaching to develop one of its transverse axis, education, sexual in young people the same as interrelates with human being. The research was based on qualitative-quantitative study….